SELF DISCLOSURE MUSLIMAH BERCADAR DI DESA LUMARING KABUPATEN LUWU (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study aims to determine (1) describing self disclosure of veiled Muslim women in Lumaring Village, Luwu Regency (2) identify and explain acceptance of veiled Muslim women in Lumaring Village, Luwu Regency. This research uses a qualitative approach with a phenomenological research method. Data collection techniques carried out by in-depth interviews with nine informants, five informants who use veils and four informants do not use veils. Data management and analysis techniques using the Huberman and Miles models. The results showed that "Self-Disclosure of Muslim Veils in Lumaring Village of Luwu Regency" (1) open self when in the community, veiled women open themselves and approach with the community so that there is no negative stigma about them (2) acceptance of veiled Muslim women in Lumaring Village, Luwu Regency, was received positively by the community because it used the veil as obedience to Allah SWT.